The Effect of Kinesiology Taping on Respiratory Muscle Strength - (:unkn) unknown (SOC PHYSICAL THERAPY SCIENCE, 2012)
[Purpose] The aim of this study was to examine the effect of kinesiology taping applied to primary and accessory respiratory muscles on respiratory muscle strength.[Subjects] The subjects were 47 healthy university students (16 female, 31 male), who were all enrolled at the Department of Physiotherapy and Rehabilitation, Faculty of Health Sciences, The University of Marmara. [Methods] Participants were divided into two groups and diaphragmatic kinesiology taping was applied to the first group and kinesiology taping to the accessory respiratory muscles of the second group. Respiratory muscle strength was measured with Micro Mouth Pressure Measurement (M PM) before and after taping.[Results] The results show that kinesiology taping of the primary and accessory respiratory muscles caused no significant increase in respiratory strength. [Conclusion] The current findings on the effect of kinesiology taping on muscular strength do not fully support the results of other studies reported in the literature. These results suggest the need for more comprehensive studies of both acute and long-term effects of kinesiology taping on muscular strength of healthy individuals and patients.
Keywords: Kinesiology taping; Respiratory muscle strength; Micro mouth pressure measurement; STERNOMASTOID MUSCLES; SCALENE; TAPE